The impact of strategic human resource development on organizational growth - Armoti, Ayman Al; Ameri, Salem Al; Hammadi, Jalal Al (Journal of Asian Business Strategy, 2023)
There is a major need to focus on all such aspects to avoid inconsistencies. It is even noticed that managing the workforce during the time of pandemic has become a real challenge for the organizations because it started to create a negative impact over the workers' productivity that eventually has begun to develop the adverse impact over the organizational growth. It is even claimed by that the high focus over the human asset developed is essential to focus to have the competent and retained workforce. The research tends to clarify the relationship between the Strategic Human Resource Development (SHRD) practices and organizational growth. However, the following research has been organized in the context of the Abu Dhabi National Oil Company (ADNOC). This research has specifically investigated determining the key SHRD practices that contribute to the organizational growth and explained how SHRD helps establishments to maximize the organizational growth of ADNOC by embracing organizational learning. The overall study has an approach to focus more on the challenges areas of organizational development within ADNOC company. The outcomes were evaluated effectively to understand the issues and factors faced by the employees who were responsible for reducing the productivity of the company toward organizational growth by focusing over the organizational development.